Application of Carbon Nanomaterials as Supports in Heterogeneous Catalysis - Mohd Sharifuddin Bin Ahmad Fuat, Mohd Sharifuddin (Universiti Teknologi Petronas, 2009)
The overall objective of this project is to investigate the application of carbon nanomaterials as support in heterogeneous catalysis. In the study, carbon nanomaterials such as single-walled carbon nanotubes (SWNTs), multi-walled carbon nanotubes (MWNTs), carbon replica of zeolites and activated carbon are proposed as support in heterogeneous catalysis. The performance of carbon nanomaterials used will be studied and the comparison with activated carbon will be made to determine the effectiveness of the carbon nanomaterials as potential support in heterogeneous catalysis. The heterogeneous distribution of the nanoparticles that will be use such as nickel, iron and cobalt were evidenced by bulk and surface structural and compositional characterizations, that is, scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction, Fourier Transform Infrared (FTIR) and thermo gravimetric analysis (TGA). The significant of the application of carbon nanomaterials will be observed with the improvement in the catalytic efficiency of the chemical reaction. Various applications of carbon nanomaterials as support in heterogeneous catalysis can be seen in pharmaceutical, electrical, optical and mechanical applications.